Telehealth to Expand Community Health Nurse Education in Rural Guatemala: A Pilot Feasibility and Acceptability Evaluation - McConnell, Kelly A.; Krisher, Lyndsay K.; Lenssen, Maureen; Bunik, Maya; Bunge Montes, Saskia; Domek, Gretchen J. (Frontiers in Public Health, 2017)
Telehealth education has the potential to serve as an important, low-cost method of expanding healthcare worker education and support, especially in rural settings of low- and middle-income countries. We describe an innovative educational strategy to strengthen a long-term health professional capacity building partnership between Guatemalan and US-based partners. In this pilot evaluation, community health nurses in rural Guatemala received customized, interactive education via telehealth from faculty at the supporting US-based institution. Program evaluation of this 10 lecture series demonstrated high levels of satisfaction among learners and instructors as well as knowledge gain by learners. An average of 5.5 learners and 2 instructors attended the 10 lectures and completed surveys using a Likert scale to rate statements regarding lecture content, technology, and personal connection. Positive statements about lecture content and the applicability to daily work had 98% or greater agreement as did statements regarding ease of technology and convenience. The learners agreed with feeling connected to the instructors 100% of the time, while instructors had 86.4% agreement with connection related statements. Instructors, joining at their respective work locations, rated convenience statements at 100% agreement. This evaluation also demonstrated effectiveness with an average 10.7% increase in pre- to posttest knowledge scores by learners. As the global health community considers efficiency in time, money, and our environment, telehealth education is a critical method to consider and develop for health worker education. Our pilot program evaluation shows that telehealth may be an effective method of delivering education to frontline health workers in rural Guatemala. While larger studies are needed to quantify the duration and benefits of specific knowledge gains and to perform a cost-effectiveness analysis of the program, our initial pilot results are encouraging and show that a telehealth program between a US-based university and a rural community health program in a low- and middle-income country is both feasible and acceptable.